Are young and old workers harmful for firm productivity? - Thierry Lallemand; François Rycx (Institute for the Study of Labor (IZA), 2009)
This paper investigates the effects of the workforce age structure on the productivity of large Belgian firms. More precisely, it examines different scenarios of changes in the proportion of young (16-29 years), middle-aged (30-49 years) and old (more than 49 years) workers and their expected effects on firm productivity. Using detailed matched employer-employee data, we find that a higher share of young (old) workers within firms is favourable (harmful) for firm value added per capita. Results also show that age structure effects on productivity are stronger in ICT than in non-ICT firms.
urn:nbn:de:101:1-2009020982
Keywords: J21; J31; L25; 330; Firm performance; workforce age structure; demographic changes; Arbeitskräfte; Altersgruppe; Produktivität; Unternehmensentwicklung; Jugendliche Arbeitskräfte; Ältere Arbeitskräfte; Belgien